Olympic Dam: BHP thinking big about the future. (December 2020) - Cuthbert, P.
Olympic Dam is one of the world's most significant polymetallic orebodies producing copper, uranium, gold, and silver in remote South Australia. The polymetallic deposit is located 520 km north-northwest of Adelaide, South Australia and has an inferred resource of 2660 Mt at 1.2% Cu, 1.4 kg t −1 U3 Os, and 0.5 g t −1 Au. Ore is mined from the underground operation at a rate of approximately 10 mt year −1, and is processed on site through a concentrator and hydrometallurgical facility, smelter, and electrolytic refinery. Olympic Dam is one of the only sites in the world to claim the 'mine to market' title. Protection of the workforce and the environment has been a primary focus for the operations through its 30+ year life and will continue to be into the future. Broken Hill Propriety Company (BHP) believes that its most important asset is its people. With such a large orebody and a very long potential mine life, it is important to think strategically about the future to ensure the viability of the operation. This requires development of mine and surface processing facilities in a staged manner. Importantly, it also involves the development of people. This presentation provides an overview of BHP's work at Olympic Dam and outlines development plans for Olympic Dam into the future. © 2020 ICRP. Published by SAGE.